Penerapan PowerPoint Media Interaktif dalam Meningkatkan Semangat dan Hasil Belajar Siswa di Kelas 4 SDN 26 Mataram - Muji, Mujiburrahman putra; Malik, Imam; Purnama, Diah Husnia (Mataram University, 2025)
The problem underlying this research is the low learning outcomes of fifth-grade students in the IPAS subject at SDN 26 Ampenan. This study aims to describe the implementation of Wordwall-based media to improve students’ learning outcomes. The approach used is qualitative with a Classroom Action Research (CAR) design consisting of two cycles, where each cycle includes two meetings with four stages: planning, implementation, observation, and reflection. The focus of this research is on the application of Wordwall-based media and students’ learning outcomes. The research subjects were the teacher and 14 fifth-grade students of SDN 26 Ampenan. Data were collected using observation sheets, tests, and documentation, and analyzed qualitatively. The results of the study showed an improvement in both teacher and student activities, as well as in students’ learning outcomes. The learning process became more engaging and interactive through the integration of Wordwall media, which provided opportunities for students to actively participate and better understand the material. It can be concluded that the implementation of Wordwall-based learning media effectively improved students’ learning outcomes in the IPAS subject for fifth-grade students at SDN 26 Ampenan.